"Competition policy" and the Doha development agenda. A position paper for the Foundation for Research, Science, and Technology - Kerrin M. Vautier (New Zealand Institute of Economic Research (NZIER), 2002)
This position paper identifies a range of elements in the international debate on `Competition Policy' that preceded the 2001 Doha Declaration. It is intended as a `scene-setter', as the WTO moves towards its pivotal fifth Ministerial meeting in Mexico in September 2003.
Keywords: 330; Wettbewerbspolitik; Internationales Wettbewerbsrecht; WTO-Regeln